2015
DOI: 10.1098/rsbl.2015.0113
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supply limits the heat tolerance of lizard embryos

Abstract: The mechanisms that set the thermal limits to life remain uncertain. Classically, researchers thought that heating kills by disrupting the structures of proteins or membranes, but an alternative hypothesis focuses on the demand for oxygen relative to its supply. We evaluated this alternative hypothesis by comparing the lethal temperature for lizard embryos developing at oxygen concentrations of 10-30%. Embryos exposed to normoxia and hyperoxia survived to higher temperatures than those exposed to hypoxia, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 17 publications
4
63
0
1
Order By: Relevance
“…This was supported by experiments that induced hypoxia by simulating flood events (Kam 1994;Tucker et al 1997). Flooding also affects temperature and moisture, both of which exert combinatorial effects on the metabolism of reptilian embryos (Kam & Lillywhite 1994;Lungman & Piña 2013;Liang et al 2015;Smith et al 2015).…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was supported by experiments that induced hypoxia by simulating flood events (Kam 1994;Tucker et al 1997). Flooding also affects temperature and moisture, both of which exert combinatorial effects on the metabolism of reptilian embryos (Kam & Lillywhite 1994;Lungman & Piña 2013;Liang et al 2015;Smith et al 2015).…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
“…3 Fisher and Burggren 2007;Dunwoodie 2009;Liang et al 2015;Lungman and Piña 2013;Smith et al 2015). In oviparous tetrapods, embryo growth may be disrupted when gaseous O 2 in the egg incubation environment decreases below normal atmospheric conditions (< 21%; hypoxia hereafter) (Stock and Metcalfe 1987;Kam 1993a;Warburton et al 1995;Dzialowski et al 2002;Parker et al 2004;Chan and Burggren 2005;Eme et al 2013;Tate et al 2015).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This transient state could be physical connections between macromolecular structures, epigenetic state of the zygotic genome or metabolic states of the embryo and warrants further detailed investigations. For example, it has been shown that hypoxia lowers the temperature at which embryonic and organismal lethality occurs and hyperoxia enhances thermotolerance (Portner, 2002; Portner and Knust, 2007; Gendelman and Roth, 2012; Verberk et al, 2013; Smith et al, 2015). It may be interesting to connect the enhanced survival and reduced heat teratogenicity to mitochondrial divisions in the developing zebrafish embryo during the heat shocks, perhaps.…”
Section: Discussionmentioning
confidence: 99%